Assessment on Relevance, Fairness, Performance, and Challenges in the Implementation of Tactical Fitness Test - Roxas, Kizzy Mae (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of the Tactical Fitness Test (TFT) among Philippine National Police – Special Action Force (PNP-SAF) personnel by analyzing socio-demographic characteristics, perceptions of relevance and fairness, performance outcomes, experienced challenges, and relationships between demographic variables and performance. Guided by Self-Determination Theory, Functional Movement Theory, and an Input–Process–Output framework, the study employed a quantitative descriptive-correlational design. Data were collected from 310 respondents selected through stratified random sampling using a structured, self-administered questionnaire with high reliability (Cronbach’s alpha = 0.892). Findings showed that respondents generally perceived the TFT as relevant, fairly designed, and aligned with operational duties, with positive views on training adequacy and policy communication. Self-reported performance across muscular strength, cardiovascular endurance, grip and core strength, and agility and coordination was rated as good, with agility emerging as the strongest domain and strength-related tasks showing relatively lower consistency. Respondents also identified challenges related to physical demands, limited training resources, psychological pressure, and environmental conditions. Significant relationships were observed between selected demographic variables and performance outcomes, indicating variability in readiness across personnel groups. The study concludes that while the TFT is a useful assessment tool, improvements in policy clarity, fairness, technical training, and implementation support are necessary. It recommends strengthening policy communication, enhancing training programs, improving testing conditions, and incorporating objective performance measures. This study aligns with SDG 3 (Good Health and Well-Being), SDG 8 (Decent Work and Economic Growth), and SDG 16 (Peace, Justice, and Strong Institutions) by promoting physical readiness, safe working conditions, and effective law enforcement systems. Its sustainability impact lies in supporting institutional, socio-economic, and community sustainability through improved operational performance, workforce health, and public safety outcomes.